Pelaksanaan Program Panah Srikandi dalam Upaya Meningkatkan Pelayanan Publik di Desa Kauman Kabupaten Bojonegoro - ningtyas, Isma Nurcahya; Arundinasari, Indira (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
Public services in Indonesia are currently undergoing changes to improve their quality and efficiency. Many government agencies have switched to digital systems to facilitate and accelerate public services online. The Kauman Village Office, Bojonegoro Regency, has implemented online public services, namely the Panah Srikandi Program, which aims to facilitate the processing of population administration documents such as e-KTP, KK, birth certificates, death certificates, KIA, and Letters of Transfer to village communities. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through interviews, observations, and documentation. This study aims to describe and analyze how successful the Implementation of the Panah Srikandi Program is in improving administrative services to village communities. The focus of this study is analyzed using the theory of policy implementation according to David C. Korten, namely Programs, Implementing Organizations, and Target Groups. The results of this study indicate that the implementation of the Panah Srikandi program in Kauman Village has been running well in accordance with the established program regulations. However, there are still problems in its implementation, such as the lack of village budget in managing e-KTP, the process of managing e-KTP which should be carried out at the village office but currently the process is carried out at the sub-district office, and the absence of door-to-door outreach services to each resident's house in the current administrative services.